PROCEDURES FOR THE ACTIONS REQUIRED TO BUILD ELECTRIC CAR CHARGING STATIONS AGAINST THE POLISH LEGAL FRAMEWORK - Marta KAŁUŻA; Grzegorz SIERPIŃSKI (Scientific Journal of Silesian University of Technology. Series Transport)
The article is an attempt to review the requirements and procedures which an investor who intends to build and commission an electric car charging station must follow. What has been highlighted is the conditions and restrictions associated with the siting of such facilities, the relevant safety requirements and the technical inspection procedures prior to the commissioning of a charging station